Efficient ray-tracing methods for propagation prediction for indoor wireless communications. - Zhong Ji (IEEE Antennas & propagation magazine.)
The application of several ray-tracing techniques, in combination with the uniform theory of diffraction, is presented for efficient prediction of propagation in the UHF (communication) band in an indoor environment. First, we improve the computational efficiency of the two-dimensional (2D) ray-tracing method by reorganizing the objects in an indoor environment into irregular cells. Second, by making use of the two-dimensional ray-tracing results, a new three-dimensional (3D) propagation-prediction model is developed, which can save 99% of the computation time of a traditional three-dimensional model. This new hybrid model is more accurate than two-dimensional models, and more efficient in computing the path loss to any point in the building than traditional three-dimensional models. In this model, reflection and refraction by layered materials, and diffraction for the corners of the walls, are considered. A patched-wall model is used to improve the accuracy of prediction in the method. Finally, a comparison between simulation and measurements shows good agreement.